Prevalensi Ektoparasit pada ikan Nila (Oreochromis niloticus) pada kolam di Kecamatan Seruyan Hilir, Kabupaten Seruyan - Sri Herlina (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2018)
This study aims to determine the types of ectoparasites that attack Tilapia (Oreocromis nilaticus) and calculate the prevalence of ectoparasite attacks on Tilapia maintained in several ponds at Seruyan Hilir District. This research was conducted from September to October 2018. This study used 30 Tilapias with 10-15 cm length which taken from several ponds. Observation of parasites was carried out using a microscope. From several samples were examined Trichodina sp was found to infect the mucus of fishes, and Ichtiyoptirius multifilis was found in mucus and fins, while Dactylogirus sp was found to infect the gills of Tilapia. Keywords : Tilapia (Oreochromis niloticus), parasites, pond, Seruyan Hilir.